Do subsidies increase charitable giving in the long run? Matching donations in a field experiment - Stephan Meier (Federal Reserve Bank of Boston, 2007)
Offering incentives to promote charitable giving (for example, to encourage donations to aid victims of natural disasters) is very popular among governments and private organizations. Many companies, for example, match their employees' charitable contributions, hoping that this will foster a strong willingness to donate. However, systematic analyses of the effect such a matching mechanism has upon voluntary giving are largely absent from the literature. Using a randomized field experiment, this paper tests the short-term and the long-run effects of matching charitable giving. The donations of a randomly selected group were matched, for one period, by contributions from an anonymous donor. The results support the hypothesis that a matching mechanism increases contributions to a public good. However, in the periods after the experiment, when matching donations have ceased, the contribution rate declines for the treatment group. In the end, the matching mechanism leads to a negative net effect on the participation rate. The field experiment therefore provides evidence suggesting that donors' willingness to contribute may be undermined by a matching mechanism in the long run.
Keywords: C93; D64; H00; 330; Public goods; field experiment; matching mechanism; charitable giving; Spende; Test; Matching; Schweiz